IDENTIFYING AND DEVELOPING STUDENTS’ INDIVIDUAL ABILITIES THROUGH BATIK ART - Kenjayeva Umida Rajabovna (O‘RTA OSIYODA IJTIMOIY VA GUMANITAR TADQIQOTLAR, 2025)
ABSTRACT: This article explores the role of batik art in identifying and developing students’ individual abilities. Batik, a traditional technique of applying wax and dye to fabric to create decorative patterns, provides students with opportunities to express creativity, discover personal talents, and enhance artistic skills. The study emphasizes the pedagogical value of using batik to observe students’ unique capabilities, including problem-solving, color perception, fine motor skills, and aesthetic judgment. Methods for guiding students to recognize and further develop their abilities through structured batik activities are discussed, highlighting the importance of individualized learning and creative self-expression. Additionally, the article examines how batik workshops foster patience, attention to detail, and perseverance, which contribute to both artistic and personal growth. Overall, batik art serves as an effective tool for educators to support the development of students’ creativity, self-confidence, and individual potential.